How to Evaluate Managerial Cognition and Avoid Traps in Open Innovation - Bhimani, Hardik; Mention, Anne-Laure; Salampasis, Dimitrios (Journal of Knowledge Management Practice, 2024)
Organisations find it difficult to assess ‘purposeful’ knowledge sourcing and sharing (KSS) for open innovation (OI), limiting full potential of KSS. We present thematic insights from 22 cognitive interviews with OI managers exploring their beliefs, perceptions, and actions during KSS activities and propose a practical framework by aggregating perception and knowledge of best practices. With illustrative quotes, a practical example case, and visual cues, we situate discussions on the common OI traps and provide clear implications for managers and organisations contemplating engaging in OI. We hope our framework provides new insights and pathways at the OI-cognition nexus.
Keywords: knowledge management; engagement; managerial cognition; open innovation; personal agency; framework